2010
DOI: 10.1152/jn.00286.2010
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Discriminate Face Views

Abstract: . Although perceptual learning of simple visual features has been studied extensively and intensively for many years, we still know little about the mechanisms of perceptual learning of complex object recognition. In a series of seven experiments, human perceptual learning in discrimination of in-depth orientation of face view was studied using psychophysical methods. We trained subjects to discriminate face orientations around a face view (i.e., 30°) over eight daily sessions, which resulted in a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
5
33
1
1
Order By: Relevance
“…This is consistent with a large literature describing a wide variety of perceptual learning effects (e.g., Ball and Sekuler 1982;Karni and Sagi 1991;Fahle and Edelman 1993;Watanabe et al 2002;Jastorff et al 2006;Bi et al 2010). The data show that, once acquired, these improvements were stable over the course of months (see also Ball and Sekuler 1987;Karni and Sagi 1993;Watanabe et al 2002;Bi et al 2014;Frank et al 2014).…”
Section: Improvements In Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with a large literature describing a wide variety of perceptual learning effects (e.g., Ball and Sekuler 1982;Karni and Sagi 1991;Fahle and Edelman 1993;Watanabe et al 2002;Jastorff et al 2006;Bi et al 2010). The data show that, once acquired, these improvements were stable over the course of months (see also Ball and Sekuler 1987;Karni and Sagi 1993;Watanabe et al 2002;Bi et al 2014;Frank et al 2014).…”
Section: Improvements In Behaviorsupporting
confidence: 91%
“…It is usually characterized by some degree of specificity to the trained stimulus attributes including stimulus location (e.g., Ball and Sekuler 1982;Karni and Sagi 1991;Poggio et al 1992;Ahissar et al 1998;Saffell and Matthews 2003;Jastorff et al 2006;Bi et al 2010), the recruitment of stimulus-specific cortical areas (e.g., Vaina et al 1998;Schwartz et al 2002;Furmanski et al 2004;Grossman et al 2004;Song et al 2010;Bi et al 2014;Frank et al 2014), as well as stability of acquired behavioral improvements over time (e.g., Ball and Sekuler 1987;Karni and Sagi 1993;Watanabe et al 2002;Bi et al 2014;Frank et al 2014). The study of perceptual learning has the potential to provide insights into neural correlates of learning more generally.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the psychological processes that underlie face perception have been the source of a great deal of scientific interest (Farah, et al, 1998; Johnston & Edmonds, 2009). Not surprisingly, many experiments have shown that our ability to identify faces significantly improves with repeated exposure and practice (Bi, Chen, Weng, He, & Fang, 2010; de Heering & Maurer, 2013; Dolan, et al, 1997; Gold, Bennett, & Sekuler, 1999b; Gold, Sekuler, & Bennett, 2004; Hussain, Sekuler, & Bennett, 2009, 2011). But what is the nature of the underlying psychological changes that take place as faces become more familiar to us?…”
Section: Introductionmentioning
confidence: 99%
“…The LVSS is independent of test viewpoints, and thus cannot be explained by the perceptual experience hypothesis, which predicts left superiority only for same views, because perceptual learning effects (or perceptual advantage) do not transfer to novel orientations and viewpoints (Bi et al, 2010;Freedman et al, 2006;Sigman & Gilbert, 2000). The LVSS cannot easily be explained by the facial asymmetry either.…”
Section: Discussionmentioning
confidence: 87%
“…The perceptual experience hypothesis predicts LVS, whatever the side of the studying sequence. However, we should not obtain an LVSS independently of test viewpoints, because perceptual experience effects are strongly specific to the orientation and viewpoint of the object, and do not transfer to novel 754 ARNOLD, BÉ CUE, SIÉ ROFF viewpoints (Bi, Chen, Weng, He, & Fang, 2010;Freedman, Riesenhuber, Poggio, & Miller, 2006;Sigman & Gilbert, 2000). According to the RH hypothesis, the LVSS may be independent of the test viewpoint.…”
mentioning
confidence: 98%